Inductive and deductive approaches to modelling of human decision making - Hollnagel, Erik (Psyke & Logos, 2023)
This paper presents the two conventional approaches to modelling of human decision making. The inductive approach emphasises the anchoring in empirical data. The deductive approach is based on accepted assumtions from formal decision theory. A comparison of the resulting models show that the outcome is very sirnilar. It is argued that this is because modeiling of decision making basically is a hermeneutical exercise, hence neither purely inductive or deductive. An adequate model of decision making in man-machine systems must be based on a description that captures the complexity of both man and machine, such as Cognitive Systems Engineering. This leads to two essential assumptions about decision making systems, that they must be both causa! and intentional. An alternate cybemetic approach to modeiling of decision making, which includes both of these assumptions, is briefly described.